2021
DOI: 10.1186/s12951-021-00884-7
|View full text |Cite
|
Sign up to set email alerts
|

NIR-II-activated biocompatible hollow nanocarbons for cancer photothermal therapy

Abstract: Photothermal therapy has attracted extensive attentions in cancer treatment due to its precise spatial-temporal controllability, minimal invasiveness, and negligible side effects. However, two major deficiencies, unsatisfactory heat conversion efficiency and limited tissue penetration depth, hugely impeded its clinical application. In this work, hollow carbon nanosphere modified with polyethylene glycol-graft-polyethylenimine (HPP) was elaborately synthesized. The synthesized HPP owns outstanding physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…In addition, the extended biomedical application as drug carrier was also achieved utilizing the large internal cavity of HPP. All the results promised the HPP as a great potential in NIR-II laser-activated cancer photothermal therapy (Xu et al, 2021). Yang et al fabricated a novel nanocarrier composed of biodegradable charged polyester vectors (BCPVs) and graphene quantum dots (GQDs) for pancreatic cancer therapy applications.…”
Section: Other Materialsmentioning
confidence: 99%
“…In addition, the extended biomedical application as drug carrier was also achieved utilizing the large internal cavity of HPP. All the results promised the HPP as a great potential in NIR-II laser-activated cancer photothermal therapy (Xu et al, 2021). Yang et al fabricated a novel nanocarrier composed of biodegradable charged polyester vectors (BCPVs) and graphene quantum dots (GQDs) for pancreatic cancer therapy applications.…”
Section: Other Materialsmentioning
confidence: 99%
“…In addition, MCNs have high efficiency in converting NIR laser energy into thermal energy and can be used in tumor PTT ( 72 , 149 ). Xu et al ( 45 ) designed polyethylene glycol-graft-polyethylenimine (HPP)-modified HCNs as NIR-II responsive PTAs. The experimental results showed that HPP-HCNs have a PCE of 45.1% under 1064nm laser irradiation.…”
Section: Classification Of Photothermal Nanomaterialsmentioning
confidence: 99%
“…As a kind of external stimulation, ultrasound has the risk of causing tumor metastasis or tissue damage under high intensity . Moreover, due to the limited therapeutic effect and the multi-drug resistance of cancer cells, chemotherapy alone often cannot completely eliminate tumor tissues, leading to tumor metastasis or regeneration. Therefore, there is a pressing demand for relatively safe stimuli-responsive NDDSs with minimal cross-reaction with other therapeutic protocols for synergistic cancer therapy.…”
Section: Introductionmentioning
confidence: 99%